2003
DOI: 10.1074/jbc.m302868200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Domains Participating in the Substrate Specificity and Subcellular Localization of the Multidrug Resistance Proteins MRP1 and MRP2

Abstract: The human multidrug resistance protein MRP1 and its homolog, MRP2, are both thought to be involved in cancer drug resistance and the transport of a wide variety of organic anions, including the cysteinyl leukotriene C 4 (LTC 4 ) (K m ‫؍‬ 0.1 and 1 M). To determine which domain of these proteins is associated with substrate specificity and subcellular localization, we constructed various chimeric MRP1/MRP2 molecules and expressed them in polarized mammalian LLC-PK1 cells. We examined the kinetic properties of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 58 publications
1
28
0
1
Order By: Relevance
“…Thus, the COOH-terminal region of MRP2 can indeed substitute for the native region of MRP1, even in the absence of MSD0. It also has been reported that the apical location of MRP2 is unaffected by exchange of MSD0 and part of CL3 for the analogous region from MRP1 (Konno et al, 2003). Consistent with this finding, we confirmed that MRP1 1-203 / MRP2 189 -1545 localized to apical membranes in the polarized MDCK-I cells used for this study (Supplementary Data Figure 3B).…”
Section: Processing and Trafficking Of Mrp1 Hybrid Proteinssupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, the COOH-terminal region of MRP2 can indeed substitute for the native region of MRP1, even in the absence of MSD0. It also has been reported that the apical location of MRP2 is unaffected by exchange of MSD0 and part of CL3 for the analogous region from MRP1 (Konno et al, 2003). Consistent with this finding, we confirmed that MRP1 1-203 / MRP2 189 -1545 localized to apical membranes in the polarized MDCK-I cells used for this study (Supplementary Data Figure 3B).…”
Section: Processing and Trafficking Of Mrp1 Hybrid Proteinssupporting
confidence: 92%
“…Processing and Trafficking of MRP1 Hybrid Proteins Recently, it has been shown that the COOH-terminal region following the Walker B motif in NBD2 of MRP1 can be exchanged for the analogous domain from MRP2 without affecting activity or plasma membrane localization (Konno et al, 2003;Westlake et al, 2004). Consequently, we determined whether this was also true in the absence of MSD0.…”
Section: Molecular Biology Of the Cell 2488mentioning
confidence: 92%
See 2 more Smart Citations
“…Whereas one report proposed that the PDZ-binding motif is the apical targeting signal of ABCC2 [46], this was not confirmed by all other studies [34, 93,124,183]. These latter studies indicate that the apical targeting motif of ABCC2 is not a distinct, narrowly defined amino acid sequence, but rather appears to be composed of several motifs within different parts of ABCC2 that come together only in the intact protein.…”
Section: Localization Of Abcc2 In Polarized Cells and Tissuesmentioning
confidence: 84%